Supporting Resources for the Successful Implementation of the Curriculum - Achmad Lutfi Affandi (CV. Publikasi Indonesia, 2025)
Education is pivotal in shaping a resilient and capable younger generation; however, many schools face challenges in effectively implementing their curricula due to insufficient support resources. The purpose of this study is to determine the resources that support the successful implementation of the curriculum. The method used by the researcher is library research in the form of references from various sources on the internet. Curriculum implementation support resources are an important aspect that must be considered in curriculum implementation efforts in schools. Effective curriculum implementation requires support and careful preparation, including adequate support resources. Some of the resources that support curriculum implementation include teaching materials, information and communication technology, facilities and infrastructure, and quality human resources. This can facilitate an effective learning process, and help teachers and students carry out a more effective and enjoyable learning process. Improve the quality of learning, help teachers present subject matter in a more interesting and innovative way so that students are more interested and eager to learn. Improve efficiency and productivity, help the learning process run more efficiently and productively so that the time and energy of students and teachers can be maximized. Supports curriculum development, can facilitate the process of curriculum development and preparation so that the curriculum can be better structured and in accordance with the needs of students and society.